COMPARATIVE EMPIRICAL ANALYSIS OF OCCUPATIONAL AND MOTIVATIONAL DIFFERENCES OF DIFFERENT GENERATION IN INDIAN WORKFORCE - Manoj Kumar Dash and Bijya Kumar Panda (Abhigyan, 2010)
Building on previous research into generational differences, this exploratory study examined whether differences in personality and motivational drivers truly exist in the workplace across different generations. Using the Occupational Personality Questionnaire and the Motivation Questionnaire as measures of personality and motivational values respectively, the study examined cross-sectional differences in three groups of working participants: Baby Boomers, Gen X's and Gen Y's. Results are not supportive of generational stereotypes that have been pervasive in the management literature and the media. Specifically, few meaningful differences were found between the three generations. Moreover, even when differences have been observed, these have related more to age rather than generational differences. More importantly, while the differences have been statistically significant, they were observed to be minimal in practical interpretation terms. . Furthermore it was intended to test empirical research gathered by a literature review of the stereotypes in the workplace, to better understand the profiles and factors that motivate the Baby Boomers and Generation X, in conjunction with the following independent variables: Achieving, Affiliative, Optimistic , Variety Seeking, Independent minded, Consciousness. This further emphasizes the importance of managing individuals by focusing on individual differences rather than relying on generational stereotypes. As was demonstrated by the survey, Baby Boomers and Generation Xers are not dissimilar as employees; they possess more similarities than differences. Organizations need to foster an environment of respect/ equity for both groups to create synergies between them to build and maintain a productive workforce.